Hypertension Treatment Rates and Health Care Worker Density: An Analysis of Worldwide Data. Issue 3 (March 2019) - Vedanthan, Rajesh; Ray, Mondira; Fuster, Valentin; Magenheim, Ellen
Abstract : Elevated blood pressure is the leading cause of death worldwide; however, treatment and control rates for hypertension are low. Here, we analyze the relationship between physician and nurse density and hypertension treatment rates worldwide. Data on hypertension treatment rates were collected from the STEPwise approach to Surveillance country reports, individual studies resulting from a PubMed search for articles published between 1990 and 2010, and manual search of the reference lists of extracted studies. Data on health care worker density were obtained from the Global Atlas of the Health Workforce. We controlled for a variety of variables related to population characteristics and access to health care, data obtained from the World Bank, World Development Indicators, United Nations, and World Health Organization. We used clustering of SEs at the country level. Full data were available for 154 hypertension treatment rate values representing 68 countries between 1990 and 2010. Hypertension treatment rate ranged from 3.4% to 82.5%, with higher treatment rates associated with higher income classification. Physician and nurse/midwife generally increased with income classification. Total healthcare worker density was significantly associated with hypertension treatment rate in the unadjusted model ( P <0.001); however, only nurse density remained significant in the fully adjusted model ( P =0.050). These analyses suggest that nurse density, not physician density, explains most of the relationship with hypertension treatment rate and remains significant even after adjusting for other independent variables. These results have important implications for health policy, health system design, and program implementation. Abstract : Supplemental Digital Content is available in the text.